Risk Analysis of Shallot Farming Production in Malang City - Putra, Hazel Pernanda; Manik, Yesaya Chrisyando (International Journal of Global Operations Research, 2024)
This research aims to determine the risk level of shallot farming and the factors that influence it in Malang City. The sample determination method used was Simple Random Sampling with a sample size of 102 respondents. The research results show that shallot farming in the research area has a high risk with factors that influence the level of production risk being the number of workers, the amount of pesticides, and the amount of NPK fertilizer. Shallot productivity in Malang City is quite high compared to the average shallot productivity in East Java.